Pembentukan Kelompok Belajar Sebagai Strategi Untuk Meningkatkan Minat Belajar Siswa SD di Desa Binaan Sos Children Village Medan Kelurahan Kwala Bekala - Ruth Indah Triani Aruan; Randa Putra Kasea Sinaga (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Community service as a manifestation of one of the Tri Dharma of Higher  Education  carried  out  by  Students  of  the  Social  Welfare Study   Program,   Faculty   of   Social   and   Political   Sciences,   the University  of  North  Sumatra  through  Practicum  II  activities  at  SOS children's village medan, through the family strengthening program carried out in  kwala bekala aimed at increasing the interest of students at the time of the pandemic, to increase their interest in learning through the formation of study groups. The method the author uses in this devotion program is community intervention by zastrow, which consists of: intake and contract, deals, planning/planning, intervention and formulation of programs, evaluations, and terminations. The results of the program can be seen from the attainment of the goals and impact students obtained during the program. Where students who participate in the program are able to follow the writer's well applied set of activities and are thus helpful in increasing their interest in learning. It is seen at the rate of their presence in group meetings each week and the results of weekly quizzes that show their willingness to repeat each home lesson.